OPTIMIZATION OF COLLECTION ROUTES USING THE CENTRE OF GRAVITY METHOD: A CASE STUDY - Ondrej STOPKA; Vladimír ĽUPTÁK; Miloš POLIAK; Mária STOPKOVÁ (Scientific Journal of Silesian University of Technology. Series Transport)
The paper deals with the implementation of research concerning the collection routes of a selected company and subsequent streamlining processes in the field of distribution logistics. Specifically, the paper is focused on the optimization of collection routes of textile waste for the customer, i.e., a contractual partner of the company under investigation. The objective of the paper is to analyse step by step the current state of logistics of supplying a specific warehouse, followed by the application of the centre of gravity method for proposing a warehouse relocation. Finally, the individual routes to collection points are optimized. In general, optimization is done for two basic reasons: profit maximization and logistics costs minimization, which ultimately has a positive impact on earnings. The outcome is to determine the optimal routes with respect to costs and traffic while considering complications that may occur in a given transport territory.